Antimicrobial compounds from natural sources - Pedro Ismael Da Silva Jr (Frontiers Research Topics, 2014)
The nature is a generous source of a number of compounds with potential application for the treatment of several diseases including the infectious diseases, which is of utmost concern for the modern medicine due to the observed striding antimicrobial resistance. A number of sources of natural compounds with valuable and clinical antimicrobial activity can be listed, comprising medicinal plants, marine and terrestrial organisms, which includes fungi and bacteria. Nevertheless, there is still a vast fauna and flora that, once systematically explored, could provide additional antimicrobial leads and drugs. Investigators were invited to contribute with original research and/or review articles on this area, specifically with studies exploiting the mechanism of action and the structure-activity aspects of natural compounds with antimicrobial activity that provides insights on potential ways to overcome the antimicrobial resistance. Therefore, thanks to the contribution of active researchers in the field, several scientific studies mainly focused on natural products with antimicrobial activity are presented in this Research Topic Ebook.